Tuning the Ising-type anisotropy in trigonal bipyramidal Co(ii) complexes. Issue 92 (6th October 2015) - Shao, Feng; Cahier, Benjamin; Guihéry, Nathalie; Rivière, Eric; Guillot, Régis; Barra, Anne-Laure; Lan, Yanhua; Wernsdorfer, Wolfgang; Campbell, Victoria E.; Mallah, Talal
Abstract : Imposing a trigonal bipyramidal geometry to a central Co(ii ) ion with long equatorial Co–S bonds results in a complex that exhibits large Ising-type anisotropy. Abstract : This paper demonstrates the engineering and tuning of Ising-type magnetic anisotropy in trigonal bipyramidal Co(ii ) complexes. Here, we predict that employing a ligand that forces a trigonal bipyramidal arrangement and has weak equatorial σ-donating atoms, increases (in absolute value) the negative zero field splitting parameter D . With these considerations in mind, we used a sulfur containing ligand (NS3 iPr ), which imposes a trigonal bipyramidal geometry to the central Co(ii ) ion with long equatorial Co–S bonds. The resulting complex exhibits a larger anisotropy barrier and a longer relaxation time in comparison to the complex prepared with a nitrogen containing ligand (Me6 tren).